Factors affecting performance of adult learners of diploma in accountancy Universiti Teknologi MARA / Anisah Mahmood, Y. Nurli Abu Bakar and Fatimah Abd Rauf - Mahmood, Anisah; Abu Bakar, Y. Nurli; Abd Rauf, Fatimah (Institute of Education Development (InED), 2007)
Adult learners are self-supporting, mature, responsible, and lead lives as independent citizens with family and career responsibilities. They are generally self-directed and interested in an institution that has the flexibility in delivery and course requirements. The objective of this study is to identify factors that affect the performance of students of diploma in accountancy (E-PJJ). Various demographic variables were identified namely gender, age, marital status, work background, and income level. Additionally, academic variables were also included namely attendance in seminars, test attendance and submission of assignments Finally, variables representing the web activities such as participation in the course forum, e-mailing the facilitators, and use of the web resources were also analysed. The findings indicated that the factors affecting the performance of adult learners can only be predicted by looking at the number of assignments submitted, and the number of additional reference materials used. Neither the demographic variables nor the academic activities variables could be the predictors or factors. Thus, for the adult learners to perform or succeed, their efforts taken and commitments are vital.